Micronucleus analysis in a portuguese population exposed to pesticides:preliminary survey - Costa, Carla (2007)
The general population is exposed in their everyday life to different chemicals namely to pesticides. Many of these compounds are capable of inducing mutations in DNA and lead to several diseases including cancer. With this study we intended to evaluate DNA damage inflicted by pesticide exposure in a population occupationally exposed to those chemicals by means of the micronucleus (MN) test. The obtained results showed a significant increase in MN frequency in occupationally exposed individuals (po0.001) compared with the control group. Higher frequencies of MN were associated with a specific workplace (greenhouses) and the lack of protective measures (gloves) during labour activities. These results reinforce that conditions in workplace should be improved to minimize exposure to these chemicals. This study also emphasizes the need to reinforce the good practices campaigns in order to enlighten those who work with pesticides on the potential hazard of occupational exposure and the importance of using protective measures.